Comparative study of SiO2 and TiO2 nanoparticles on flow and heat transfer of dusty fluid over a stretching sheet. Issue 5 (2nd September 2019) - Kumar, K. Ganesh; Archana, M.
Abstract : Purpose: The purpose of this paper is to model the boundary layer flow and heat transfer of dusty fluid with suspended nanoparticles over a stretching surface. The effect of multiple slip and nonlinear thermal radiation is taken into the account. Adequate similarity transformations are used to obtain a set of nonlinear ordinary differential equations to govern formulated problem. The resultant non-dimensionalized boundary value problem is solved numerically using the RKF-45 method. The profiles for velocity and temperature, which are controlled by thermophysical parameters, are presented graphically. Based on these plots, the conclusion is given and the obtained numerical results are tabulated. Observed interesting fact is that the SiO2 -water nanoparticles show a thicker thermal boundary layer than TiO2 -water nanoparticles. Design/methodology/approach: The governing partial differential equations are approximated to a system of nonlinear ordinary differential equations by using suitable similarity transformations. An effective fourth–ﬁfth-order Runge–Kutta–Fehlberg integration scheme numerically solves these equations along with a shooting technique. The effects of various pertinent parameters on the flow and heat transfer are examined. Findings: Present results have an excellent agreement with previous published results in the limiting cases. The values of skin friction and wall temperature for different governing parameters are also tabulated. It is demonstrated that the SiO2 -water nanoparticles show a thicker thermal boundary layer than TiO2 -water nanoparticles. It is interesting to note that the dusty nanofluids are found to have higher thermal conductivity. Originality/value: This paper is a new work related to comparative study of TiO2 and SiO2 nanoparticles in heat transfer of dusty fluid flow.